Brand Revitalization: Penciptaan Brand Image Produk Green Sands Bebas Alkohol melalui Marketing Communication (Advertising dan Public Relation) pada PT Multi Bintang Indonesia Tb - Adhikara, Cooky Tri; Nurparamesti, Sindy Kusuma (Binus Business Review, 2011)
PT Multi Bintang Indonesia is a beverages production company, and one of its products are Green Sands. In early 2002, Green Sands revitalize to Green Sands Alcohol-Free and communicated through several promotional tools, including advertising and public relations. This study examines what brand image embedded on the consumers, and what is the level of influence of advertising and public relations toward the creation of brand image of products Green Sands Alcohol-Free. The research methods used in this study is test Cochran, multiple regression, and cobwebs. The result, brand image that is embedded in consumer brand is cool and trendy and unique and refreshing taste. Advertising and public relations by creating a brand image is only 7.2%, the rest from other factors. Brand image is embedded in the customers had not yet reached the desired scale of the company.Â